SPECTRUM OF MINE BLAST OCULAR INJURIES: Mine Blast Ocular Injuries - Islam, Maj Qamar Ul (Pakistan Armed Forces Medical Journal, 2010)
Objective: To describe the pattern of injuries and common ocular manifestations due to landmine explosion in patients evacuated to Combined Military Hospital Pano Aqil.Study Design: Prospective, observational case series.Place and Duration of Study: Eye Department, CMH Pano Aqil from Jan 2006 to Aug 2007. Patients and Methods: Thirty seven consecutive patients with mine blast ocular injuries were evaluated for types, pattern and extent of ocular damage. A detailed ophthalmic examination was carried out and all the relevant information was endorsed on a pre devised proforma. Patients were managed conservatively or surgically according to their ocular condition.